Economic aspects of browse development. The economic viability of browse plantations in tropical Africa. A study following the symposium on browse in Africa - International Livestock Centre for Africa (1981)
Examines economic aspects of browse development, w. data on browse, wood, gum and crop production, international rate of return and cost prices on atriplex and acacia plantations in tropical Africa.